Public expenditure analysis for social protection in Sri Lanka - Nicolò Bird; Ganga Tilakaratna; Louise Moreira Daniels; Shilohni Sumanthiran; Élise Chrétien; Krista Alvarenga; Pedro Arruda (International Policy Centre for Inclusive Growth (IPC-IG), 2022)
As policymakers gradually (re-)assess social protection systems in the wider context of recovery from the COVID-19 pandemic, it is becoming increasingly important to have clear information on country-level programmes. This Research Report examines the country's existing non-contributory (social assistance) and (semi-)contributory (social insurance) social protection programmes.
Keywords: 330; Social protection; social insurance; Sri Lanka; COVID-19; pandemic recovery